Eradication of Helicobacter pylori and Gastric Cancer: A Controversial Relationship - Piscione, Mariagrazia; Mazzone, Mariangela; Di Marcantonio, Maria Carmela; Muraro, Raffaella; Mincione, Gabriella (Frontiers in Microbiology, 2021)
Gastric cancer (GC) is at present the fifth most common cancer worldwide for incidence, and the third leading cause of death in developed countries. Indeed, it resulted in more than 780,000 deaths in 2018. Helicobacter pylori is considered to be responsible for the majority of these cancers. On the basis of recent studies, and either alone or combined with additional etiological factors, H. pylori has been widely identified as a “type I carcinogen”. Over recent decades, new insights have been obtained into the strategies that have been adopted by H. pylori to adapt to the extreme acidic conditions of the gastric environment, to establish persistent infections, and to deregulate host functions. The development of GC is a multistep process initiated by transition of the normal mucosa to chronic non atrophic gastritis, triggered primarily by H. pylori infection. This gastritis can progress to atrophic gastritis, intestinal metaplasia, and finally to dysplasia and adenocarcinoma (Correa’s cascade). Antibiotic-mediated eradication of H. pylori reduces incidence of precancerous lesions only in the early stages of gastric carcinogenesis. Here, we first survey the etiology and risk factors of GC, and then we analyze the mechanisms underlying tumorigenesis induced by H. pylori, focusing attention on virulence factor CagA, inflammation, oxidative stress, and ErbB2 receptor tyrosine kinase. Moreover, we investigate the relationships between H. pylori eradication therapy and other diseases, considering not only cardia (upper stomach) cancers and Barrett’s esophagus, but also asthma and allergies, through discussion of the ‘hygiene hypothesis’. This hypothesis suggests that improved hygiene and antibiotic use in early life reduces microbial exposure, such that the immune response does not become primed, and individuals are not protected against atopic disorders, asthma, and autoimmune diseases. Finally, we overview recent advances on the complex interplay between the gut microbiota and H. pylori during gastric carcinogenesis, as characterized by reduced bacterial diversity and increased microbial dysbiosis. Indeed, it is of particular importance to identify the groups of bacterial taxa in the stomach that might be predictive of the outcome of gastric disease at specific stages along Correa’s cascade, to improve the prevention and therapy of gastric carcinoma.